Some factors influencing serum triglyceride in man - Mann, Joel Ivor (Division of Human Nutrition, 2020)
Part I of this thesis deals with general methodology and the experimental work can be clearly divided into two sections. Part II deals with studies carried out chiefly to determine further the epidemiological factors influencing serum lipid (and in particular, serum triglyceride) levels in the population groups of Southern Africa. The original objectives are described on page 70 and the main conclusions summarised on page 114. Part III describes three studies which were conducted in an attempt to fill some of the gaps in the considerable literature on the relationship between dietary carbohydrate and serum lipids in man. Both in the review of the literature at the beginning of this section and in the interpretation of the results of each of the studies, discussion has been chiefly limited to experiments conducted in man. There is a great deal of information available on studies carried out in experimental animals which show marked species differences from man with regards kinetic behaviour of serum and liver triglycerides(l). Where relevant, of course, reference has been made to these studies. The significance of each of the three studies has been discussed separately, but the principal objectives are mentioned on page 138 and the general conclusions are summarised on page 205.